The Effect of Job Satisfaction and Job Achievement on Work Productivity of Denkav-5/BLC XVI/Pattimura Personnel - Maryoto Maryoto; Ferikawita Magdalena Sembiring (Komando (Kompetensi Manajemen dan Organisasi): Bisnis dan Pertahanan, 2024)
Absences from military activities for an extended period of time are a violation of discipline and can result in a decline in unit productivity if not addressed. This phenomenon is prevalent in all Army units, influenced by the mindset of the soldiers. This study examines the relationship between job satisfaction, work performance, and work productivity, as well as the impact of job satisfaction, work performance, and both factors on work productivity. The research was conducted at Denkav-5/BLC Kodam XVI/Ptm in Ambon. This study employs quantitative methodologies. Information is derived from both primary and secondary sources. Additional sources of data were gathered through the administration of surveys and the examination of relevant literature. The Slovin formula resulted in a total of 174 replies. Data were measured using a Likert scale. Analysis of multiple linear regression was conducted. This study revealed that workplace happiness exerts both positive and negative influences on work productivity parameters, whereas work performance exerts a negligible impact. While accomplishment exerts a relatively minor influence on productivity, job satisfaction and performance exert a simultaneous effect on work productivity.